OPTIMALISASI LABEL DAN KEMASAN MELALUI PENDAMPINGAN PADA USAHA KRIPIK PISANG OZEN DI DUSUN KARANGNONGKO BARAT - Wardhani, Ayu Era; Saphira, Naila Ayu; Putri, Elvina Fauzia; Huda, Khoiriyatul Kamilatul (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
Micro, small and medium businesses (UMKM) have an important role in the local economy, but often face challenges in marketing aspects, including packaging label design and information. This research aims to optimise packaging labels through a mentoring programme for the Ozen Banana Chips business in Karangnongko Barat Village. The approach used includes needs an analysis, redesign of packaging labels, and evaluation of their effectiveness on consumer appeal. The results of the mentoring programme showed that a more informative, attractive label design that complies with regulatory standards increases buyer interest and strengthens product identity in the market. In addition, packaging label optimisation also contributes to improving business competitiveness and opening wider marketing opportunities. With this assistance, it is hoped that the UMKM can further develop and compete more professionally in the snack food industry.